"We were treated like adults"—development of a pre-medicine summer school for 16 year olds from deprived socioeconomic backgrounds: action research study. Issue 7544 (22nd February 2006) - Greenhalgh, Trisha; Russell, Jill; Boynton, Petra; Lefford, Frances; Chopra, Nikhil; Dunkley, Lisa
Abstract: Objective To develop a one week widening access summer school for 16 year old pupils from non-traditional backgrounds who are considering applying to medical school, and to identify its short term impact and key success factors. Design Action research with partnership schools in deprived inner city areas in five overlapping phases: schools liaison, recruitment of pupils and assessment of needs, programme design, programme delivery, and evaluation. The design phase incorporated findings from one to one interviews with every pupil, and workshops and focus groups for pupils, parents, teachers, medical student assistants, NHS staff, and other stakeholders. An in-depth process evaluation of the summer school was undertaken from the perspective of multiple stakeholders using questionnaires, interviews, focus groups, and observation. Participants 40 pupils aged 16 years from socioeconomically deprived and under-represented ethnic minority groups. Results The summer school was popular with pupils, parents, teachers, and staff. It substantially raised pupils' confidence and motivation to apply to medical school. Critical success factors were identified as an atmosphere of "respect"; a focus on hands-on work in small groups; the input of medical students as role models; and vision and leadership from senior staff. A particularly popular and effective aspect of the course was a grand round held on the last day, in which pupils gave group presentations of real cases. Conclusion An action research format allowed us to draw the different stakeholders into a collaborative endeavour characterised by enthusiasm, interpersonal support, and mutual respect. The input from pupils to the programme design ensured high engagement and low dropout rates. Hands-on activities in small groups and social drama of preparing and giving a grand round presentation were particularly important.